Fatigue damage evolution mechanism of sandstone under Freeze–Thaw and loading rate coupling based on NMR and AE techniques - Shen, Dekang; Wang, Xing; Yang, Daoxue (Frontiers in Earth Science, 2026)
The influence of freeze-thaw damage effects on the fatigue mechanical response characteristics and damage mechanisms of sandstone was examined. Three loading rates (0.2, 0.4, and 0.6 kN/s) and four freeze-thaw cycles (0, 15, 30, and 45 cycles) were used in cyclic loading-unloading tests to accomplish this. The sandstone’s physical parameters, pore structure evolution, stress-strain behavior, and microcrack propagation characteristics were all carefully examined using nuclear magnetic resonance and acoustic emission techniques. The findings showed that the mass of saturated sandstone rose by 0.26% over the first 15 freeze-thaw cycles. However, the mass dropped by 0.17% and 1.01%, respectively, when the number of freeze-thaw cycles reached 30 and 45. The percentage of macropores increased from 45% to 63% after 45 cycles, suggesting that frost heave forces encouraged the spread of microcracks and the formation of linked fissures, which progressively weakened the structure. The loading rate also played a big influence. In comparison to a rate of 0.2 kN/s, a greater loading rate (0.6 kN/s) reduced slow crack development, increasing the cyclic strength by 14.8%. The strength degradation rate surpassed 24% when the number of freeze-thaw cycles reached 30 or more, indicating that even at high loading rates, freeze-thaw damage continued to be the primary cause. Microcracks started to appear at 15 cycles, with tensile cracks outnumbering shear cracks. However, the percentage of shear cracks rose with increasing loading rates, almost equaling or even exceeding that of tensile cracks. The connectivity between pores and cracks greatly improved with 30 and 45 cycles, and high loading rates were more likely to induce rapid and abrupt instability behavior by favoring shear crack dominance. Under identical freeze-thaw circumstances, increasing loading rates increased the ratio of shear cracks, demonstrating that local stress distributions altered crack propagation routes. This study provides theoretical insights for evaluating the stability of rock engineering in cold climates by elucidating how loading rates and cyclic freeze-thaw processes govern the fatigue mechanical behavior of sandstone.